Archaeological excavations in the Buenavista site (Lanzarote): New information for the study of the protohistoric colonization of the Canary Archipelago - Atoche Peña, Pablo (Gerión. Revista de Historia Antigua, 2012)
The archaeological works carried out at Buenavista (Lanzarote) have shown a big rectangular structure inside an stratigraphic sequence with a number of artifacts and chronology fluctuating between 10th Century BC and 3rd Century AD. The dates are new for Canarian protohistory, as well as the fact that organic remains associated to Phoeno-Punic materials (pottery, copper and bronze objects and a glass seed) have been found. The goal of this paper is to present a synthesis of the archaeological works at Buenavista showing stratigraphy, chronology and material record.